(untitled) (Global Journal of Human-Social Science, 2021)
This study assessed morphometric of gullies in Nasarawa State Soil erosion is among the most endemic environmental problems of modern times Both primary and secondary sources of data were used for this study As ample of 36 gully sites were carried out in three Local Government Areas representing the study area for this research work Information on gullies morphometric morphology soil particles size and the coordinate of each identified gullies site were taken from the field Instruments such as hand auger global position system GPS photograph Abeny level linen tape ranging poles pegs and measuring tape and field observation methods were also adopted The results generated from the field were subjected to statistical and laboratory analysis The results of the findings revealed that 44 4 of the gullies in the study area are discontinuous gullies 55 6 were continuous gullies while gullies in the study are at their 5 and above development 58 3 of the sampled gullies were at a stable state of development while 41 7 of the gullies were at an unstable state of development It was also revealed that 38 9 of the sampled gullies in the study area were long-narrow gullies while 22 2 were linear shaped gullies